Real-Time Imaging of Short-Wave Infrared Luminescence Lifetimes for Anti-counterfeiting Applications - Ziniuk, Roman; Yakovliev, Artem; Li, Hui; Chen, Guanying; Qu, Junle; Ohulchanskyy, Tymish Y. (Frontiers in Chemistry, 2021)
Rare-earth doped nanoparticles (RENPs) have been widely used for anti-counterfeiting and security applications due to their light frequency conversion features: being excited at one wavelength, they display spectrally narrow and distinguished luminescence peaks either at shorter wavelengths (i.e., frequency/energy upconversion) or at longer wavelengths (frequency/energy downconversion). RENPs with a downconversion (DC) photoluminescence (PL) in short-wave infrared (SWIR) spectral range ( 1000-1700 nm) have recently been introduced to anti-counterfeiting applications, allowing for multilevel protection based on PL imaging through opaque layers, due to a lesser scattering of SWIR PL emission. However, as the number and spectral positions of the discrete PL bands exhibited by rare-earth ions are well known, it is feasible to replicate luminescence spectra from RENPs, which results in a limited anti-counterfeiting security. Alternatively, lifetime of PL from RENPs can be used for encoding, as it can be finely tuned in broad temporal range (i.e., from micro to milliseconds) by varying type of dopants and their content in RENPs, along with the nanoparticle morphology and size. Nevertheless, current approach to decoding and imaging of the RENPs luminescence lifetimes requires multiple steps and is highly time-consuming, precluding practical applications of PL lifetime encoding for anti-counterfeiting. Herein, we report the use of a rapid lifetime determination (RLD) technique to overcome this issue and introduce real-time imaging of SWIR photoluminescence lifetime for anti-counterfeiting applications. NaYF4:20% Yb, x% Er (x= 0, 2, 20, 80)@NaYF4 core@shell RENPs were synthesized and characterized, revealing DC PL in SWIR region, with maximum at 1530 nm and PL lifetimes ranging from 3.2 to 6 ms. Imaging of the nanoparticles with different lifetimes was performed by the developed time-gated imaging system engaging RLD method and the precise manipulation of the delay between the excitation pulses and camera gating windows. Moreover, it is shown that imaging and decrypting can be performed with high rate (3-4 fps) in a cyclic manner, thus allowing for real-time temporal decoding. We believe that the demonstrated RLD based fast PL lifetime imaging approach can be employed in other applications of photoluminescent RENPs.